Probing the stability and magnetic properties of magnetosome chains in freeze-dried magnetotactic bacteria. Issue 3 (4th March 2020) - Bender, Philipp; Marcano, Lourdes; Orue, Iñaki; Alba Venero, Diego; Honecker, Dirk; Fernández Barquín, Luis; Muela, Alicia; Fdez-Gubieda, M. Luisa
Abstract : Magnetospirillum gryphiswaldense biosynthesize high quality magnetite nanoparticles, called magnetosomes, and arrange them into a chain that behaves like a magnetic compass. Abstract : Magnetospirillum gryphiswaldense biosynthesize high-quality magnetite nanoparticles, called magnetosomes, and arrange them into a chain that behaves like a magnetic compass. Here we perform magnetometry and polarized small-angle neutron scattering (SANS) experiments on a powder of freeze-dried and immobilized M. gryphiswaldense . We confirm that the individual magnetosomes are single-domain nanoparticles and that an alignment of the particle moments along the magnetic field direction occurs exclusively by an internal, coherent rotation. Our magnetometry results of the bacteria powder indicate an absence of dipolar interactions between the particle chains and a dominant uniaxial magnetic anisotropy. Finally, we can verify by SANS that the chain structure within the immobilized, freeze-dried bacteria is preserved also after application of large magnetic fields up to 1 T.